2009
DOI: 10.1002/nvsm.369
|View full text |Cite
|
Sign up to set email alerts
|

‘Just don't eat chicken’: the challenge of engaging Australian adults in appropriate preventive behaviours for bird flu

Abstract: Leading medical experts have cautioned about the risk of inappropriate behavioural responses as a result of fear of avian influenza (bird flu) even before a pandemic emerges, and have emphasised the need for appropriate risk communication strategies. There is a paucity of in‐depth qualitative research into the general public's understanding of, and reactions to, such potential health crises. Four focus groups were conducted in April 2006 and a further eight focus groups in July 2006, to examine people's knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…failed almost immediately with widespread dissemination just 20 days after its being declared a quarantinable disease” (Kotsimbos et al , 302). Policy failures included screening practices expecting typical flu symptoms, nonisolation of exposed cruise passengers, testing limited to people who had traveled only to affected locations, continuation of national sporting events, public perceptions that H1N1 was mild, and insufficient communication between health officials and citizens (Eastman et al ; Fogarty et al ; Grayson and Johnson ; Holland and Blood ; Jones, Iverson, and Waters ; Seale et al ; Waterer, Hui, and Jenkins ). The Australian Medical Association criticized the government for “being too slow, creating fever clinics at major hospitals only when GPs’ surgeries were overrun” and not quickly distributing stockpiles of personal protective equipment (Eizenberg ; Rouse ).…”
Section: Refocusing On Human Health Pandemics and Quarantinable Diseasesmentioning
confidence: 99%
“…failed almost immediately with widespread dissemination just 20 days after its being declared a quarantinable disease” (Kotsimbos et al , 302). Policy failures included screening practices expecting typical flu symptoms, nonisolation of exposed cruise passengers, testing limited to people who had traveled only to affected locations, continuation of national sporting events, public perceptions that H1N1 was mild, and insufficient communication between health officials and citizens (Eastman et al ; Fogarty et al ; Grayson and Johnson ; Holland and Blood ; Jones, Iverson, and Waters ; Seale et al ; Waterer, Hui, and Jenkins ). The Australian Medical Association criticized the government for “being too slow, creating fever clinics at major hospitals only when GPs’ surgeries were overrun” and not quickly distributing stockpiles of personal protective equipment (Eizenberg ; Rouse ).…”
Section: Refocusing On Human Health Pandemics and Quarantinable Diseasesmentioning
confidence: 99%
“…Consumer perception is narrated as action and reaction on what one sees (Kotler et al 2005). It may be said after assembling the two ideas, thatadvertising is the leading force in charge of forming purchasers' perceptions and inducing a behavioral reaction (Jones, Iverson, & Waters, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Primary among these are: more frequent and thorough hand washing; the use of disposable tissues rather than handkerchiefs; and the wearing of a face mask if experiencing symptoms or exposed to others with symptoms. In an Australian survey conducted in relation to avian influenza, the majority of respondents expressed a willingness to comply with the first two of these behaviors; there was reluctance to engage in the third [18,19]. However, while these behaviors appear to be simple and doable, the research has identified some problems with both the communication and the acceptance of these behaviors (such as "washing their hands" as thoroughly and frequently as needed).…”
Section: Promote a Single Doable Behavior Explained In Simple Cleamentioning
confidence: 99%
“…This need to reduce the level of physical contact between individuals and groups also carries with it considerable social cost, as does engaging in some of the more visible protective behaviours. Thus, it was not surprising that Australian research in the context of avian influenza found that many people are willing to engage in some personal protective behaviour (such as using disposable tissues) but are resistant to changing public or social behaviours (such as wearing face masks and not shaking hands) [18,19]. It is interesting to note that acceptance of these strategies in the event of an outbreak was higher in US-based surveys [20,21]; those living in the US would have more recent and direct experience of pandemic/ epidemic infections (such as SARS), further demonstrating the need for social marketing strategies to understand the knowledge and attitudes of specific target audiences.…”
Section: Understand and Address Perceived Benefits And Costsmentioning
confidence: 99%
See 1 more Smart Citation